Anthocyanin-Rich Blackcurrant Supplementation as a Nutraceutical Ergogenic Aid for Exercise Performance and Recovery: A Narrative Review - Mark ET Willems; Sam D Blacker; Stefano Montanari; Matthew D Cook (Current Developments in Nutrition)
Athletes and physically active individuals consume sport nutrition supplements to enhance competitive sport performance and exercise recovery. Polyphenols have emerged as a promising area of research with application for sport and exercise nutrition owing to affecting physiologic mechanisms for exercise performance and recovery. The anthocyanin is a polyphenol that can be abundantly present in dark-colored fruits, berries, and vegetables. Anthocyanins and anthocyanin-induced metabolites will provide antioxidant and anti-inflammatory effects. The focus of this narrative review was on the observations with intake of anthocyanin-rich blackcurrant supplements on whole-body exercise performance and exercise recovery. This review included 17 studies with a randomized placebo-controlled crossover design (10 studies on performance and 8 on recovery effects) and 1 with a randomized placebo-controlled parallel group design (recovery effects). Among the performance studies, 6 studies (60%) reported positive effects, 3 studies (30%) reported no significant effects, and 1 study (10%) reported a mixed outcome. Among the recovery studies, 7 studies (78%) reported positive effects, 1 study (11%) reported no significant effects, and 1 study (11%) reported a negative effect. Studies with intake of supplements made from New Zealand blackcurrants (dose: 1.8–3.2 mg/kg and 105–315 mg anthocyanins, acute to 7-d intake) provided meaningful (but not always consistent) effects on continuous and intermittent exercise performance tasks (i.e. rowing, cycling, and running) and markers for exercise recovery. A mechanistic understanding for the beneficial exercise effects of anthocyanins for athletes and physically active individuals is still limited. Future work requires a better understanding of the specific types of anthocyanins and anthocyanin-induced metabolites and their effects on altering cell function that can enhance exercise performance and recovery.